The Influence of Absorptive Capacity on SMEs Performance In Padang City Mediated By Strategic Agility - Reynaldo, Ratu meisya; Thabrani, Gesit (Human Resource Management Studies, 2025)
This study aims to analyze the effect of absorptive capacity on the performance of Small and Medium Enterprises (SMEs) in Kota Padang, with strategic agility as a mediating variable. Absorptive capacity is defined as the ability of SMEs to identify, absorb, and apply external knowledge, which is believed to play an essential role in improving business performance. Meanwhile, strategic agility is the ability of SMEs to adapt quickly and flexibly to changes in the business environment, which is hypothesized to strengthen the relationship between absorptive capacity and SME performance.This study uses a quantitative method with a survey technique involving 201 SME owners in Kota Padang. Respondents were selected based on several criteria, such as the number of employees, daily revenue, sources of business capital, and business duration.